2009
DOI: 10.1677/erc-09-0084
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of novel germline deletions affecting SDHD and SDHC in pheochromocytoma and paraganglioma patients

Abstract: A major cause of paraganglioma and pheochromocytoma is germline mutation of the tumor suppressor genes SDHB, SDHC, and SDHD, encoding subunits of succinate dehydrogenase (SDH). While many SDH missense/nonsense mutations have been identified, few large deletions have been described. We performed multiplex ligation-dependent probe amplification deletion analysis in 126 point mutation-negative patients, and here we describe four novel deletions of SDHD and SDHC. Long-range PCR was used for the fine mapping of del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Both MLPA [67] and similar multiplex PCR methods [68] have been applied in SDH deletion analysis, and have led to the recognition that deletions can represent up to 10% of all mutations [69]. …”
Section: New Strategies In Mutation Analysismentioning
confidence: 99%
“…Both MLPA [67] and similar multiplex PCR methods [68] have been applied in SDH deletion analysis, and have led to the recognition that deletions can represent up to 10% of all mutations [69]. …”
Section: New Strategies In Mutation Analysismentioning
confidence: 99%
“…In 2007, Pasini et al reported in some familial GIST patients, germline mutations in the succinate dehydrogenase subunits SDHB, SDHC, and SDHD [21]; SDH mutations had been previously reported in patients with familial paraganglioma [22]. SDH subunit A mutations have also recently been implicated in GIST [Pantaleo MA, JNCI 2011; Pantaleo MA, Am J Surg Pathol 2011][23].…”
Section: Introductionmentioning
confidence: 99%
“…For example, MIRb is one of the enriched repeat elements. MIRb insertion was reported to be involved in paraganglioma and pheochromocytoma which are associated with germline mutation of the tumour suppressor genes [32]. …”
Section: Resultsmentioning
confidence: 99%